Perceptions held by University of Limpopo agricultural students towards self- employment in agribusiness - Dlamini, Bheki Prince (My University, 2022)
This study was aimed at analyzing the perception of students towards selfemployment in agribusiness. Primary data was collected at the University of Limpopo using questionnaires from five disciplines in the School of Agriculture and Environmental Science (SAES). The study population was final year undergraduate, stratified random sampling procedure was used to select seventy-one (71) respondents from the cluster of departments within SAES. Descriptive statistics such as frequency count, percentage and mean score on a Likert-type of scale and Chisquared test were used to address various objectives of the study. Results of the study indicated that most respondents were aged between 21-27 years old, a majority of them were doing a degree in animal production, most of the students were females, majority come from households with 4-6 family members, many come from rural areas, most of the students had no relatives owning a business, most of the respondents had no access to farming land, and about half of the respondents had no farming experience. Respondents had a positive perception towards self-employment in agribusiness with them agreeing on statements like farmers are notable people, entrepreneurship is effective in reducing unemployment, farming is sustainable and disagreeing with statements like farming is for poor people, profitability in farming is very low, that they prefer other degrading jobs than engaging in agriculture. The results also show that most of the students preferred starting facilitation and agency of agricultural insurance savings, followed by poultry enterprise and provision of extension consultancy services. The study also found that most of the motivator’s motivating respondents to pursue self-employment include that agricultural related enterprises are very lucrative, also that many South Africans have made a lot of fortunes from agriculture and that agriculture in South Africa has a lot of untapped potential. The barriers include that agriculture is a risky business enterprise in South Africa and that it is not easy to create self-employment in agribusiness. It was also found that perceived barriers and motivators were highly associated with the type of degree students were studying. The study recommended that the University of Limpopo curriculum must have a module dealing with agriculture venture creation related to the degree and be more practically based. The University of Limpopo also has to invite entrepreneur's guest lecture for their students and produce more research on how to promote youth participation in agriculture especially establishing agribusiness. Development of easily accessible ready-to-market and agricultural commodity distribution centers will inspire more young people to move into farming. First preference needs to be given to agriculture graduates when offering sponsorship, grants and agribusiness loans.
Thesis (M. Agricultural Management (Agricultural Extension)) -- University of Limpopo, 2022
Keywords: Agricultural programmes; Youth and agriculture; Perception; Agricultural entrepreneurship; Agri-business; Self-employment; Agricultural extension work; Agricultural industries; Agricultural students; Agriculture -- Economic aspects; Part-time self-employment